2020
DOI: 10.1111/aas.13596
|View full text |Cite
|
Sign up to set email alerts
|

Data quality of Glasgow Coma Scale and Systolic Blood Pressure in scientific studies involving physician‐staffed emergency medical services: Systematic review

Abstract: BackgroundEmergency physicians on‐scene provide highly specialized care to severely sick or injured patients. High‐quality research relies on the quality of data, but no commonly accepted definition of EMS data quality exits. Glasgow Coma Score (GCS) and Systolic Blood Pressure (SBP) are core physiological variables, but little is known about the quality of these data when reported in p‐EMS research. This systematic review aims to describe the quality of pre‐hospital reporting of GCS and SBP data in studies wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…We relied on AIS, NISS, and GCS score less than 9 to determine injury severity, although we appreciate that more data about vital signs would bring valuable information. This was not available because of incomplete registration of prehospital data, a challenge for many registries and services 43 . The indication for performing or not performing time-critical interventions is not registered in the NTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We relied on AIS, NISS, and GCS score less than 9 to determine injury severity, although we appreciate that more data about vital signs would bring valuable information. This was not available because of incomplete registration of prehospital data, a challenge for many registries and services 43 . The indication for performing or not performing time-critical interventions is not registered in the NTR.…”
Section: Discussionmentioning
confidence: 99%
“…This was not available because of incomplete registration of prehospital data, a challenge for many registries and services. 43 The indication for performing or not performing time-critical interventions is not registered in the NTR. Instead, we used measures with a high likelihood of indication for interventions, such as injury stratification and GCS score less than 9 and assessed all AIS codes associated with potential need for CD.…”
Section: Discussionmentioning
confidence: 99%
“…In the records analyzed in this study, an overall high level of complete documentation was found, although there were several individual parameters that need more consistent documentation (49% availability for data on the respiration rate, temperature and blood glucose level). In past studies, the percent of cases with adequate RR documentation varied from 10–40%, and a recent systematic review on data quality in EMS reported that there were deficiencies in the completeness and accuracy of the reporting 35 37 . Therefore, the documentation of tele-EMS missions appears to be of relatively higher quality in terms of the completeness of the data.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Challenges with heterogeneous data have previously been reported in the prehospital setting. 12 Lee reported on the varying definitions of timeline in different transport services and networks. 6 A medical field which has used templates to guide research and quality improvement initiatives is cardiac arrest, with the Utstein template.…”
Section: Introductionmentioning
confidence: 99%